Effect of visual marbling levels in pork loins on meat quality and Thai consumer acceptance and purchase intent - Noidad, Sawankamol (Asian-Australas J Anim Sci, 2019)
OBJECTIVE: We investigated visual marbling level (VML) influence on pork loin physicochemical traits, consumer palatability responses, VML liking, purchase intent, and their relationships. METHODS: For each of five slaughtering dates, at 24-h postmortem, nine paired Duroc castrated male boneless Longissimus dorsi (LD) muscles were categorized into low (LM, score 1 to 2, n = 3), medium (MM, score 3 to 4, n = 3), and high (HM, score 5 to 6, n = 3) VML. Meat physicochemical quality traits and consumer responses (n = 389) on palatability and VML liking, and purchase intent were evaluated. The experiment was in randomized complete block design. Analysis of variance, Duncan’s multiple mean comparisons, and correlation coefficients were determined. RESULTS: VML correspond to crude fat (r = 0.91, p<0.01), but both were reversely related to moisture content (r = −0.75 and −0.91, p<0.01, respectively). As VML increased, ash (p<0.05) and protein (p = 0.072) decreased, pH and b* increased (p<0.05), but drip, cooking (p<0.05) and thawing (p = 0.088) losses decreased. Among treatments, muscle fiber diameter, sarcomere length, total and insoluble collagen contents, L*, and a* did not differ (p>0.05). Compared to the others, HM had lower collagen solubility percentage (p<0.05), but similar (p>0.05) Warner-Bratzler shear force (WBSF). No differences (p>0.05) were found in juiciness, overall flavor, oiliness, and overall acceptability, but HM was more tender (p<0.05) than the others. Based on VML, consumers preferred MM to HM (p<0.05), while LM was similar to MM and HM (p>0.05). Corresponding to VML preference (r = 0.45, p<0.01), consumers (83%) would (p<0.01) definitely and probably buy MM, over LM (74%), and HM (68%), respectively. CONCLUSION: Increasing VML in pork LD altered its chemical composition, slightly increased pH, and improved water holding capacity, thereby improving its tenderness acceptability. Marbling might reduce chewing resistance, as lower collagen solubility in HM did not impact tenderness acceptability and WBSF. While HM was rated as most tender, consumers visually preferred and would purchase MM.